Di(2-ethylhexyl) phthalate mediates IL-33 production via aryl hydrocarbon receptor and is associated with childhood allergy development - Tsai, Mei-Lan; Hsu, Shih-Hsien; Wang, Li-Ting; Liao, Wei-Ting; Lin, Yi-Ching; Kuo, Chang-Hung; Hsu, Ya-Ling; Feng, Ming-Chu; Kuo, Fu-Chen; Hung, Chih-Hsing (Frontiers in Immunology, 2023)
Background Few studies assess cord blood biomarkers to predict prenatal exposure to di(2-ethylhexyl) phthalate (DEHP) on the development of allergic diseases later in childhood. IL-33 has been indicated to play an important role in allergic diseases. We evaluated the association of prenatal DEHP exposure and IL-33 in cord blood on the development of allergic diseases. We also investigated the mechanism of DEHP in human lung epithelial cells and asthma animal models. Methods 66 pregnant women were recruited, and their children followed when they were aged 3 years. Maternal urinary DEHP metabolites were determined using liquid chromatography-electrospray-ionization-tandem mass spectrometry. The effect of DEHP on IL-33 production was investigated in human lung epithelial cells and club cell-specific aryl hydrocarbon receptor (AhR) deficiency mice. ELISA and RT-PCR, respectively, measured the IL-33 cytokine concentration and mRNA expression. Results The concentrations of maternal urinary DEHP metabolites and serum IL-33 in cord blood with childhood allergy were significantly higher than those in the non-childhood allergy group. DEHP and MEHP could induce IL-33 production and reverse by AhR antagonist and flavonoids in vitro. Enhanced ovalbumin-induced IL-4 and IL-33 production in bronchoalveolar lavage fluid (BALF) by DEHP exposure and suppressed in club cell-specific AhR null mice. Kaempferol has significantly reversed the DEHP effect in the asthma animal model. Conclusions Cord blood IL-33 level was correlated to childhood allergy and associated with maternal DEHP exposure. IL-33 might be a potential target to assess the development of DEHP-related childhood allergic disease. Flavonoids might be the natural antidotes for DEHP.